Pregled seča - makroskopski in mikroskopski pregled seča ter kemična analiza seča s testnimi lističi - Kersnik-Levart, Tanja (Medicinski razgledi, 2007)
Urinalysis is a very simple and inexpensive test which, when correctly interpreted, is an invaluable diagnostic tool in the diagnosis if many urologic and non-urologic diseases. This review article presents urine macroscopic and microscopic examination and urine reagent dipstick test. The differential diagnostic consideration of various urinalysis findings is also described.
Keywords: Urin, analiza; Urinalysis; Celica, štetje; Hematuria; Cell Count; Bakteriurija; Proteinurija; Bacteriuria; Hematurija; Proteinuria; Kristali; Crystallins; Reagent Strips; Reagentni trakovi; seč; diagnostika; analiza